Parents as partners in black schools: so important, but why so unreliable? - Heystek, J. (Koers, 1999)
Parents and schools are partners in the education of children because schools are a form a lised extension of the family, when it comes to the education of children. This partnership is also emphasised by recent legislation, like the South African Schools Act of 1996. This partnership is in line with the mission of parents to educate their children or assist in the education of their children. In spite of this demand for parental involvement in schools, the research in black schools underlying this article indicates that p a rental involvement in most black school activities is limited. Reasons like a negative attitude of parents towards schools and feelings of inferiority prevents parents to become effective partners of schools. The reasons for the lack of active participation in school activities and some possible solutions will receive attention in this contribution.